Natural Cycle Frozen Embryo Transfer: Evaluating Optimal Protocols for Preparation and Timing - Kai N. Holder; Jessica S. Mormol; Jennifer B. Bakkensen; Mary Ellen Pavone; Kara N. Goldman; Chen Yeh; Lutfiyya N. Muhammad; Lia A. Bernardi (Journal of Human Reproductive Sciences)
Background: While natural cycle frozen embryo transfer (NC-FET) is becoming increasingly common, significant practice variation exists in the use of ovulation induction medications, administration of ovulation trigger, and timing of embryo transfer without consensus as to the optimal protocol. Aims: The objective of this study is to evaluate the association of key aspects of the NC-FET protocol with implantation, pregnancy and live birth. Settings and Design: This was a retrospective cohort study of blastocyst stage NC-FET cycles from October 2019 to July 2021 at a single academic fertility centre. Materials and Methods: Protocols varied between cycles across three key parameters which were evaluated as primary predictors of cycle outcomes: (1) use of letrozole for mild ovarian stimulation/ovulation induction, (2) administration of exogenous ovulation trigger versus spontaneous luteinising hormone surge and (3) transfer timing based on ovulation trigger versus sequential progesterone monitoring. Primary outcomes included implantation rate, clinical pregnancy and ongoing pregnancy. Statistical Analysis Used: Generalised estimating equations were fitted to obtain adjusted odds ratios or rate ratios as appropriate with 95% confidence intervals for each outcome across the three primary predictors. Results: A total of 183 cycles from 170 unique patients were eligible for inclusion. The average implantation rate was 0.58, resulting in an overall clinical pregnancy and ongoing pregnancy rate of 59.0% and 51.4%, respectively. After adjusting for age at embryo freeze and history of a failed embryo transfer, there were no significant associations between any predictor and implantation rate, clinical pregnancy, ongoing pregnancy, or live birth. Conclusion: In NC-FET, a variety of preparation and timing protocols may lead to comparable cycle outcomes, potentially allowing for flexibility on the basis of patient and physician preference. These findings warrant validation in a larger, randomised trial.